Preoperative sCD40L levels predict risk of atrial fibrillation after off-pump coronary artery bypass graft surgery. - Antoniades, C; Van-Assche, T; Shirodaria, C; Diesch, J; Antonopoulos, A; Lee, J; Cunnington, C; Tousoulis, D; Stefanadis, C; Casadei, B; Taggart, D; Channon, K; et al. (2009)
BACKGROUND: The risk of atrial fibrillation (AF) after coronary bypass surgery has been related to redox state, inflammation, and ischemia. Platelet activation is common to all of these pathways. We investigated the relation between AF and preoperative soluble CD40 ligand (sCD40L), a proinflammatory marker released by activated platelets. Furthermore, we studied the role of inflammation, endothelial function, and redox state in this relation. METHODS AND RESULTS: sCD40L levels were measured in 144 patients in sinus rhythm the day before off-pump coronary artery surgery. Systemic inflammation was assessed from levels of C-reactive protein and soluble intercellular adhesion molecule-1, and endothelial function was assessed from the brachial artery flow-mediated dilatation response. Graft samples were collected during surgery to assess vascular redox state. AF occurred in 33% of patients after surgery, with 3% still in AF after 6 weeks. Preoperative sCD40L levels were significantly higher in those who developed in-hospital AF (odds ratio for a 1-SD increase in log[sCD40L]=1.97; 95% CI, 1.21 to 3.22; P=0.007; after adjustment for age, sex, Euroscore, and total duration of operation). sCD40L and vascular superoxide levels were higher in patients still in AF at 6 weeks, and endothelial function was lower, although the small number of events precluded statistical analysis in this group. Systemic endothelial function, redox state, and preoperative markers of systemic inflammation were not associated with in-hospital postoperative AF. CONCLUSIONS: Preoperative platelet activation, as assessed by sCD40L levels, is a novel predictor of postoperative AF, independent of systemic endothelial function, vascular redox state, and systemic inflammation.